Need for sexual education in school. (Journal of Parents and Teachers, 2014)
This article explains the importance of educating in sexuality in the school offering a definition of the same and important data such as the acquisition of sexual identity or what the children know about sexuality.
Keywords: Sexuality; sexual education.